[PLDT ; Cry rape ; Flying high [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
Deals with the announcement of PLDT about their policy of opening interconnection even with its competitors; women's group questining the rape law hoping that the lawmakers will amend it to prevent injustices done to women who are victims of heinous crimes against chastity; and the story on sky diving as exciting sport in the Philippines.
PLDT (18 min.) -- Cry rape (19 min.) -- Flying high (12 min.)
VHS.
Keywords: Philippine Long Distance Telephone Company; Telephone -- Philippines; Rape victims -- Philippines; Skydiving -- Philippines